A Chromosomal-Level Genome of Dermatophagoides farinae, a Common Allergenic Mite Species - Rongxuan Hu; Haifeng Huang; Ying Zhou; Yanshan Liu; Yaning Ren; Yuanfen Liao; Cunyin Yuan; Xiaohong Gu; Yubao Cui (International Journal of Genomics)
Background. Genome data have been used to find novel allergen from house dust mites. Here, we aim to construct a chromosome-level genome assembly of Dermatophagoides farinae, a common allergenic mite species. Methods. We achieved a chromosome-level assembly of D. farinae’s genome by integrating PacBio single-molecule real-time sequencing, Illumina paired-end sequencing, and Hi-C technology, followed by annotating allergens and mapping them to specific chromosomes. Results. A 62.43 Mb genome was assembled with a 0.52% heterozygosity rate and a 36.11 Merqury-estimated quality value. The assembled genome represents 92.1% completeness benchmarking universal single-copy orthologs with a scaffold N50 value of 7.11 Mb. Hi-C scaffolding of the genome resulted in construction of 10 pseudochromosomes. The genome comprises 13.01% (7.66 Mb) repetitive sequences and predicts 10,709 protein-coding genes, 96.57% of which are functionally annotated. Moreover, we identified and located 36 allergen groups on specific chromosomes, including allergens Der f 1, Der f 2, Der f 23, Der f 4, Der f 5, Der f 7, and Der f 21 located on chromosomes 2, 1, 7, 3, 4, 6, and 4, respectively. Conclusion. This comprehensive genomic data provides valuable insights into mite biology and evolutionary adaptations, potentially advancing D. farinae allergy research and treatment strategies.